THE INFLUENCE OF BRAND PERSONALITY, BRAND AWARENESS, FASHION CONSCIOUSNESS, AND SATISFACTION AS INTERVENING VARIABLES ON MUSLIM FASHION PRODUCT LOYALTY IN INDONESIA - Zukhrufani, Alfitri; Ratnasari, Ririn Tri (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
This research is intended to formulate a conceptual framework to determine the effect of the relationship between brand personality, brand awareness, fashion consciousness, and consumer satisfaction of Muslim women on Muslim fashion product loyalty. This research method is quantitative, with data collected by an online questionnaire and a variable measurement scale applied to a Likert scale. A sample is chosen through a purposive sampling technique, with characteristics respondents of Indonesian Muslim women who have bought and or used Muslim fashion products more than 1-2 times. The number of samples collected and successfully analyzed by as many as 155 of the 163 respondents since about eight questionnaires contained missing data. The study adopts the partial least square as a method of analysis, using SmartPLS 3.0 software. The study results show that brand personality influences consumer satisfaction for Indonesian Muslim women but has no effect on loyalty to Muslim fashion products. Brand awareness and fashion consciousness both affect the satisfaction of Indonesian Muslim women consumers and loyalty to Muslim fashion products.JEL: M30, M310, M370.